Workshop on Recent Advances in Concrete Testing and Repair Technology / Ir. Dr. Ng Kok Shien - Ng, Kok Shien (Unit Penerbitan FKAPP, 2020)
Faculty of Civil Engineering (FCE), UiTM Cawangan Pulau Pinang in collaboration with RNC Repair Specialist Sdn Bhd had successfully conducted a two-and-a-half-day workshop on Recent Advances in Concrete Testing and Repair Technology from 17 until 19 February 2020. The workshop aimed to provide a platform for the dissemination of information in relation to recent advances in concrete testing, repair, protection and maintenance. This workshop had attracted 27 participants from construction industry comprised mainly of consultants, authorities, contractors and suppliers. The knowledge was transferred through lectures given by invited speakers and hands- on in the laboratory session. There were six invited speakers who shared their knowledge and experience in this workshop. Three of them are UiTM lecturers, namely Assoc. Prof. Dr. Noorsuhada Md Nor, Assoc. Prof. Dr. Kay Dora Abd Ghani and Dr. Muhd Norhasri Muhd Sidek. Another 3 speakers invited from the industry are Ir. Parnam Singh from RNC, Mr. Kam Kim Ang from Control Synergy and Ir. Ng Kok Seng, former director of division in JPS.